Public lands acquisition and compensation practice in Nigeria - Uduehi, Godfrey O. (Ogba, Ikeja, Nigeria : John west publications, 1987)
The book was written to alleviate the plight of students and others (Estate Surveyors, who may be faced with lack of good indigenous books on land acquisition and compensation as there are not may books written on the subject.
Includes bibliographies and index.
opc 10/01/17
Loans
Keywords: Government purchasing of real property; Public lands; Real property; Nigeria